2014
DOI: 10.1016/j.cortex.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Egocentric representations of space co-exist with allocentric representations: Evidence from spatial neglect

Abstract: The brain transforms sensory input to motor coordinates to accommodate for changes of posture and gaze direction. Neurophysiological and neuropsychological evidence supports the existence of multiple representations of space. A debated issue regards whether objects that we see are encoded in egocentric frames only or also maintain an object-centered frame of reference. Previous clinical studies were unable to discriminate between these models as the stimuli used to determine object-based (allocentric) biases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
1
17
2
Order By: Relevance
“…On the other hand, individuals with spatial neglect show a pathologically long attentional blink (Shapiro et al, 2017) which might indicate non-spatial perceptual deficit. Furthermore, the present data is consistent with our companion studies suggesting that trunk position can influence the object-based deficits seen in neglect (Karnath et al, 2011; Li et al, 2014). Individuals with spatial neglect can ignore both the left side of the observers trunk (egocentric deficits) as well as the left side within individual objects (allocentric deficits).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, individuals with spatial neglect show a pathologically long attentional blink (Shapiro et al, 2017) which might indicate non-spatial perceptual deficit. Furthermore, the present data is consistent with our companion studies suggesting that trunk position can influence the object-based deficits seen in neglect (Karnath et al, 2011; Li et al, 2014). Individuals with spatial neglect can ignore both the left side of the observers trunk (egocentric deficits) as well as the left side within individual objects (allocentric deficits).…”
Section: Discussionsupporting
confidence: 92%
“…some patients have pure egocentric deficits, while others have pure allocentric deficits; Marsh and Hillis, 2008), whereas others argue that these symptoms associate (with differences between allocentric and egocentric biases reflecting strategic decisions by the patient; Karnath & Niemeier, 2002; Baylis et al, 2004). We observed that neglect of an object’s left side was more severe at contralesional egocentric, trunk-centered positions and ameliorated continuously towards more ipsilesional egocentric positions (Karnath et al, 2011; Li et al, 2014). …”
Section: Discussionmentioning
confidence: 70%
“…Here, in the allocentric only patients we did not find any evidence for an egocentric exploration bias. This contradicts the theory proposed by Li and colleagues [15] that allocentric neglect appears due to an overall spatial gradient (Figure 1). Instead we suggest that our findings provide strong behavioural evidence for truly dissociable neglect types.…”
Section: Discussioncontrasting
confidence: 91%
“…Taking an alternative view, ego-and allocentric neglect may reflect two aspects of a central underlying disorder [12], where allocentric neglect is simply occurring when the attentional window is narrowed to a single object [13] or where allocentric biases are modulated by their egocentric position [14,15]. Relatively strong correlations between ego-and allocentric neglect have been reported [16] and it has been argued that the two cannot be fully dissociable given findings where the allocentric deficit was worse for stimuli in the contralesional compared to the ipsilesional side, supporting the notion that allocentric biases occur due to a spatial gradient of attentional weights (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…To know where to look, grasp, or move about in the cabin, astronauts must visually recognize landmarks that allow them to infer their self-orientation with respect to surrounding objects, since the notion of a (vestibular) ''gravitational down'' is meaningless [4]. Likewise neurological patients with a spatial hemineglect, which involves the vestibular cortex, have both object-based allocentric and body-centered egocentric impairment of spatial awareness [5]. Similar findings were seen in patients after an acute unilateral vestibular loss [6].…”
Section: Dear Sirsmentioning
confidence: 99%